POSTOPERATIVE COMPLICATIONS IN GENERALIZED PERITONITIS: Prediction and Immunoprophylaxis - Rakhimov, O.U. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Generalized peritonitis remains a critical challenge in abdominal surgery due to its high morbidity and mortality, especially in the early postoperative period. The complexity of immune responses, intra-abdominal contamination, and systemic inflammation contributes to a high risk of postoperative complications. This review focuses on current approaches to predicting and preventing these complications, particularly the role of immunological markers and immunomodulatory interventions. The use of scoring systems, laboratory predictors, intraoperative findings, and early immune profiling is discussed as a means to stratify risk and guide therapy. Immunoprophylaxis strategies, including perioperative immunonutrition, cytokine modulation, and selective immunotherapy, are analyzed in the context of evidence-based practice. The article highlights the importance of integrated prognostic-immunological models for improving outcomes in patients undergoing surgery for generalized peritonitis.